Optimization of phosphorus level for effective arbuscularmycorrhizal activity in rainfed upland rice based cropping system - MANOJ KUMAR BARNWAL, DIPANKAR MAITI* and (Indian Phytopathology, 2012)
Direct seeded upland rice (Oryza sativa L.), grown under aerobic soil conditions of rainfed, drought prone ecology is constrained by poor phosphorus (P) acquisition. Arbuscular-mycorrhiza (AM) supportive rice based crop rotations under this AM favorable ecology was demonstrated to improve AM aided P nutrition in upland rice. The present investigation aimed at optimizing P dose for possible further enhancing native AM-fungi (AMF) aided P acquisition of upland rice under AM supportive crop rotations. Under highly AM supportive, two year crop rotation of ‘maize (Zea mays L.) relay cropped by horse gram (Dolichos biflorus L.) in first year followed by rice in second year’, 20 kg P2O5/ha (to rice) enhanced AMF population (+79%) in soil during rice sowing (June), leading to significantly higher average (two years) AMF colonization (+15.3 %), P uptake (+10.1%) with concomitant increase in grain yield (+30.4%) over that of recommended dose (30 kg P2O5/ha).